2019
DOI: 10.48550/arxiv.1908.08730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lessons from fitting the lowest order energy independent chiral based $\bar{K}N$ potential to experimental data

János Révai

Abstract: It is shown, that fitting parameters of a KN interaction model to different sets of experimental data can lead to physical conclusions which might provide a deeper insight into the physics of this multichannel system. The available experimental data are divided into three parts: the "classical" set consisting of the low-energy K − p cross sections and the threshold branching ratios, the SIDDHARTA 1s level shift in kaonic hydrogen and the CLAS photoproduction data. We have fitted the parameters of a recently in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…As a different dataset and fitting approach was used in [5] the χ 2 /dof taken from this earlier publication cannot be compared directly with the χ 2 /dof obtained for our current models. We also note that no χ 2 /dof was provided in [1] but the same author presented χ 2 /dof in more extendend fits performed later in [20]. The parameter values obtained in our fits are reasonable, in particular the meson decay constants of both BC models and of the JR 2 one are in agreement with predictions of other analyses [40], [41].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As a different dataset and fitting approach was used in [5] the χ 2 /dof taken from this earlier publication cannot be compared directly with the χ 2 /dof obtained for our current models. We also note that no χ 2 /dof was provided in [1] but the same author presented χ 2 /dof in more extendend fits performed later in [20]. The parameter values obtained in our fits are reasonable, in particular the meson decay constants of both BC models and of the JR 2 one are in agreement with predictions of other analyses [40], [41].…”
Section: Resultssupporting
confidence: 87%
“…In a recent publication [1] (see also [20]), J. Révai criticized a procedure commonly used to simplify the solution of the above-mentioned integral equations, namely, the so-called on-shell factorisation which reduces the integral equation to an algebraic equation that can be solved immediately. Solving a Lippmann-Schwinger equation (LSE) without applying this approximation, the author of [1] obtained a kernel without energy dependence (an advantageous feature for few-body calculations), and found that the solution ".…”
Section: Introductionmentioning
confidence: 99%